2013
DOI: 10.1101/lm.031427.113
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose responsiveness, learning success, and task specialization in ants

Abstract: Social insects possess remarkable learning capabilities, which are crucial for their ecological success. They also exhibit interindividual differences in responsiveness to environmental stimuli, which underlie task specialization and division of labor. Here we investigated for the first time the relationships between sucrose responsiveness, behavioral specialization, and appetitive olfactory learning in ants, including reproductive castes. We show that castes of the ant Camponotus aethiops differ in their resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 24 publications
4
33
0
Order By: Relevance
“…Finally, our results corroborate previous studies showing that ants learn efficiently when subjected to differential conditioning of the MaLER Perez et al, 2013), thus allowing a fine-tuned investigation of their discrimination ability between two odor stimuli, one appetitive (sucrose) and the other aversive (quinine, for a discussion about the aversive valence of quinine for ants, see Guerrieri and d'Ettorre, 2010). We also confirmed that C. aethiops ants retained the associations between CSs and USs for at least 1 h .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, our results corroborate previous studies showing that ants learn efficiently when subjected to differential conditioning of the MaLER Perez et al, 2013), thus allowing a fine-tuned investigation of their discrimination ability between two odor stimuli, one appetitive (sucrose) and the other aversive (quinine, for a discussion about the aversive valence of quinine for ants, see Guerrieri and d'Ettorre, 2010). We also confirmed that C. aethiops ants retained the associations between CSs and USs for at least 1 h .…”
Section: Discussionsupporting
confidence: 90%
“…The binary response (MaLER: YES/NO) is simple and unambiguous and ants show excellent learning performances Guerrieri et al, 2011;Bos et al, 2013;Perez et al, 2013Perez et al, , 2015. Here, we used the MaLER paradigm to test whether ants were able to discriminate between different concentrations of the same hydrocarbon (linear and branched alkanes) in a differential conditioning paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a higher number of patrilines is beneficial for thermal regulation, as bees from different patrilines engage in fanning activity at different deviations from the optimal temperature, thereby providing a gradual and more efficient response to outside temperature changes [13]. In a social insect colony, the different patrilines are not equally involved in the different tasks [60][62] and workers performing different tasks show different associative learning abilities (appetitive modality: [63][64]; aversive modality: [30]). It will now be important to compare appetitive and aversive learning abilities in different patrilines and to relate these differences with the tasks these individuals actually carry out in the hive.…”
Section: Discussionmentioning
confidence: 99%
“…Medium-sized foragers were collected and anaesthetized on ice for harnessing in individual holders as previously described [14,35]. Fixed ants could only move their antennae and mouthparts.…”
Section: Methodsmentioning
confidence: 99%
“…Controlled olfactory conditioning protocols have been established for ants, which allow training them under absolute or differential conditioning, i.e. with a single stimulus rewarded (the conditioned stimulus, CS+), or with one stimulus rewarded (CS+) and another stimulus non-rewarded or punished (CS−) [2730,3335]. Both protocols have been used to investigate olfactory learning and generalization in ants, but no comparative study has been undertaken to determine the specific influence of experimental procedures on these abilities.…”
Section: Introductionmentioning
confidence: 99%